Two new species of the simulium (simulium) variegatum species-group of black flies (Diptera: Simuliidae) from Thailand - Hiroyuki Takaoka (2018)
© The Authors 2017. Two new species of black flies, Simulium (Simulium) srisukai and S. (S.) kiewmaepanense, are described from specimens collected in Thailand. Both species are assigned to the Simuliumvariegatum species-group of the subgenus Simulium (Simulium) Latreille. They are characterized by the darkened female femora and tibiae and six inflated pupal gill filaments, and the darkened female tibiae and six ordinary thread-like pupal gill filaments, respectively. Taxonomic notes are given to separate these new species from 10 related species among the group. These new species represent the third and fourth species of the S. variegatum species-group from Thailand.